Increases in heart rate and serum cortisol concentrations in healthy dogs are positively correlated with an indoor waiting‐room environment. (21st January 2014) - Perego, Roberta; Proverbio, Daniela; Spada, Eva
<x xml:space="preserve">Abstract</x> Background Few studies have investigated the effect of veterinary clinical procedures on the welfare of dogs, with specific emphasis on the veterinary practice environment. Clinicopathologic variables have also not been assessed in these potentially stressful situations. Similar to human clinical studies, the veterinary clinical waiting room could present a significant stress factor for dogs. Objectives The present study was designed to investigate the effect of waiting‐room environment on serum cortisol and glucose alterations as well as heart rate in privately owned healthy dogs. Methods The clinical trial included 24 healthy dogs that were divided into 2 groups: the clinical waiting‐room group (A) and the control group (B) that waited outside in a garden. During the entire experiment, 18 dogs (9 dogs per group) were monitored with a human heart rate monitor fastened around the chest. After 20 minutes of waiting, blood samples were collected from all of the dogs (24 dogs) to determine serum cortisol concentration. Results Serum cortisol concentration and mean, maximum, and minimum heart rate were significantly higher in group A compared with group B, but there was no statistical difference in serum glucose concentrations between the 2 study groups. Conclusions Results of this study suggest that the waiting room is a potentially stressful situation for dogs in clinical veterinary practice, when compared with a garden, based on the assessment of adrenal cortex function and heart rate evaluation.